Gambaran Diri Penderita Kusta di Puskesmas Kunduran Kabupaten Blora Jawa Tengah - Simamora, Kornelia B; Pangastuti, Heny Suseani; Effendy, Christantie (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2007)
Please refer to the file